Editorial overview: recommendations for the promotion of a resilient linefishery in the Anthropocene. Issue 3 (1st October 2020) - Potts, WM; Attwood, CG; Cowley, PD; Childs, A-R; Winkler, AC; Duncan, MI; Murray, TS; Mann, BQ; Mann-Lang, JB
Abstract : 'Linefish' is a uniquely South African term used to describe marine fishes that are captured using hook and line. The South African linefishery is a complex socio-ecological system that has a considerable impact on the coastal marine environment while generating social and economic benefits for commercial, small-scale and recreational fishers. Like many fisheries, this complex system is under threat from the combined impacts of increasing levels of exploitation and climate change associated with the Anthropocene. The Southern African Marine Linefish Symposium (SAMLS) provides a platform for linefish scientists, managers, conservation officers, individuals from nongovernmental organisations, and other stakeholders to meet and exchange knowledge about the state and development of linefisheries. This overview discusses some of the long-term trends in linefish research during the last five symposia and highlights salient outcomes of the 5th SAMLS, which was held in July 2019. While the recovery and management success for some of South Africa's commercial linefish species are recognised, the lack of policy and management in the recreational sector will not only undermine the implementation of the country's new small-scale fisheries policy, but also the resilience of the socio-ecological system. To promote a resilient linefishery in the Anthropocene it is recommended that the fishery policies be strengthened to cover all sectors in the linefishery and that the general principles of the ecosystem approach to fisheries, including the incorporation of the human dimension and the implementation of co-management, are promoted. Improved communication between fishers, scientists, and managers is necessary, and recreational permit revenue should be used for research and monitoring to improve the management and stock assessment of species important to the recreational and small-scale sectors.